(untitled) (Abhat Journal, 2025)
Abstract: The study aims to reveal the morphometric characteristics of Wadi Al-Raml Basin, represented by the area, shape, topography and drainage network characteristics, and to analyze the spatial relationships between the characteristics and deduce the most important morphometric variables of the basin, with the production of hydrological maps of the basin that help understand the characteristics of the valley. This is done by relying on the digital elevation model (DEM). The study followed the analytical, quantitative and descriptive approach in order to analyze and extract morphometric data from the digital elevation model. The study came out with a set of results, the most prominent of which is that the area of Wadi Al-Raml Basin is 242 km2, which is a small area compared to the area of other valleys, and that the valley passes through three terrain areas, which are the mountainous area, the plain area and the sloping area between the Tarhuna Mountains and the coastal plain. The maximum length of the valley reached 41 km, and the shape of the valley tends to be elongated, as the elongation of the valley basin indicates that the basin is passing through the beginning of the erosion cycle, where regressive erosion processes prevail along the course. The ruggedness ratio in the Wadi Al Raml basin reached (12.4), which is a high ratio indicating that the valley is in the early stages of the erosion cycle. As for the discharge density in the valley, it reached (1.8), which is a low density due to the small area of the upper sources of the basins in relation to the total area.